Analisis Pengaruh Kualitas Sistem Online Single Submission (OSS), Kompensasi, Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai : (Studi Kasus pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Manokwari) - Iriani, Yunita Dinda; Numberi, Camelia L.; Marlino, Marlina; Wanma, Alvany T. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study was conducted to examine the influence of the Online Single Submission (OSS) system quality, compensation, work environment, and job satisfaction on employee performance. The research sample comprised all staff within the Investment and Integrated One-Stop Service Office in Manokwari Regency, totaling 57 individuals, including 23 civil servants and 34 contract workers. Employing a quantitative approach, the study relied on primary data gathered through questionnaires distributed directly to the respondents identified for this research. Hypothesis testing was conducted using SPSS version 26. The findings of this study reveal that the variables of compensation, work environment, and job satisfaction each exert a positive and significant influence on employee performance. In contrast, the OSS system quality variable showed no significant effect on employee performance, which can be attributed to shortcomings in its implementation. These results underscore the need for management to establish more effective policies aimed at enhancing employee performance by improving compensation systems, emphasizing work environment factors, and addressing job satisfaction. Moreover, the insights derived from this research present an opportunity for future studies to explore additional factors contributing to employee performance within the public sector, offering a foundation for continuous improvement in administrative and operational efficiency. Keywords: OSS System Quality, Compensation, Work Environment, Job Satisfaction, Employee Performance